A review of cognitive screening tools in cancer. Issue 1 (March 2017) - Isenberg-Grzeda, Elie; Huband, Helen; Lam, Henry
Abstract : Purpose of review: Cancer-related cognitive impairment (CRCI) is highly prevalent, and assessment of cognition is crucial in providing optimal cancer care. Neuropsychological assessment (NPA) can be lengthy and expensive. Cognitive screening tools are plenty but validity has not been thoroughly studied for use in cancer patients. Recent findings: Our search of the recent literature revealed that the Montreal Cognitive Assessment, Mini–Mental State Examination, and Clock Draw Test were the most frequently studied objective screening tools. The Functional Assessment of Cancer Therapy-Cognitive Function and the Cognitive Symptom Checklist-Work 21 were the most commonly studied subjective measures of perceived cognitive impairment. Evidence supports using the Montreal Cognitive Assessment or the Clock Draw Test over the Mini–Mental State Examination to screen for cognitive impairment within specific patient populations. In addition, adding a subjective measure of cognitive impairment (e.g., Functional Assessment of Cancer Therapy-Cognitive Function) may increase diagnostic sensitivity. Summary: These suggest that cognitive screening tools may have a role in screening for CRCI, particularly when full NPA is not feasible. Researchers must continue to conduct high-quality studies to build an evidence to guide best practices in screening for CRCI. Abstract : Supplemental Digital Content is available in the text